Young bilingual children in nursery schools - Thompson, Linda, 1949- (Bilingual education and bilingualism, 2000)
"This book presents the findings of an ethnolinguistic study carried out in the northeast of England into the language and social behaviour of a group of three-year-old children during their first term in formal education. The children are third generation British, born into families of settled migrants who speak languages other than English in their homes and communities." "Although the study was located in the UK where English is the national and societal language, the findings (and research methods used) have implications for children in other societies where English is the formal language of education. The book will be of interest to parents, teachers and others concerned with the lives of young children."--Jacket